Multiplexed fluorescence microscopy reveals heterogeneity among stromal cells in mouse bone marrow sections. Issue 9 (14th August 2018) - Holzwarth, Karolin; Köhler, Ralf; Philipsen, Lars; Tokoyoda, Koji; Ladyhina, Valeriia; Wählby, Carolina; Niesner, Raluca A.; Hauser, Anja E.
Abstract: The bone marrow (BM) consists of multiple, structured micro‐environmental entities—the so called niches, which contain hematopoietic cells as well as stromal cells. These niches fulfill a variety of functions, such as control of the hematopoietic stem cell pool, differentiation of hematopoietic cells, and maintenance of immunological memory. However, due to the molecular and cellular complexity and a lack of suitable histological multiplexing methods, the composition of the various BM niches is still elusive. In this study, we apply multiepitope‐ligand‐cartography (MELC) on bone sections from mice. We combine multiplexed immunofluorescence histology data with various object‐based segmentation approaches in order to define irregularly shaped, net‐like structures of stromal cells. We confirm MELC as a robust histological method and validate our automated segmentation algorithms using flow cytometry and manual evaluation. By means of MELC multiplexing, we reveal heterogeneous expression of leptin receptor (LpR), BP‐1, and VCAM‐1 in the stromal network. Moreover, we demonstrate by quantification a preferential contact of B cell subsets as well as of plasma cells to processes of CXCL12‐expressing stromal cells, compared with stromal somata. In summary, our approach is suitable for spatial analysis of complex tissue structures.